MAT‐Index: An index for fast multiple aspect trajectory similarity measuring. Issue 2 (20th January 2022) - de Souza, Ana Paula Ramos; Renso, Chiara; Perego, Raffaele; Bogorny, Vania
Abstract: The semantic enrichment of mobility data with several information sources has led to a new type of movement data, the so‐called multiple aspect trajectories . Comparing multiple aspect trajectories is crucial for several analysis tasks such as querying, clustering, similarity, and classification. Multiple aspect trajectory similarity measurement is more complex and computationally expensive, because of the large number and heterogeneous aspects of space, time, and semantics that require a different treatment. Only a few works in the literature focus on optimizing all these dimensions in a single solution, and, to the best of our knowledge, none of them proposes a fast point‐to‐point comparison. In this article we propose the Multiple Aspect Trajectory Index, an index data structure for optimizing the point‐to‐point comparison of multiple aspect trajectories, considering its three basic dimensions of space, time, and semantics. Quantitative and qualitative evaluations show a processing time reduction of up to 98.1%.